A Porous POSiSil Suited for Pressure‐Driven Reversible Confinement of Solutions: PSS‐2. Issue 56 (19th September 2019) - Smet, Sam; Verlooy, Pieter; Pulinthanathu, Sreeprasanth; Kirschhock, Christine E. A.; Taulelle, Francis; Breynaert, Eric; Martens, Johan A.
Abstract: Polyoligosiloxysilicone (POSiSil; designated PSS‐2) is a copolymer of double four‐ring (D4R) cyclosilicate and dimethylsiloxane. It is synthesized by linking D4R units in tetrabutylammonium cyclosilicate crystals with dimethyldichlorosilane. The structure of PSS‐2 was revealed using solid state NMR spectroscopy. In this 3D copolymer D4R units are connected systematically by short siloxane chains most likely composed of 2 to 3 dimethylsiloxane monomers. Controlling the conversion of the parent material allows for tuning the porosity of PSS‐2. Residual parent material is embedded inside PSS‐2 polymer and can be eliminated by calcination. This leaves nanovoids inside PSS‐2, which is moderately hydrophobic. Pressure‐driven intrusion–extrusion cycles of aqueous solution exhibit hysteresis, thus, PSS‐2 can be used as reversible confinement for liquids with a capacity of around 1000 mm 3  g −1 in porosity. Abstract : The copolymer PSS‐2 (polyoligosiloxysilicone) consists of double four‐ring (D4R) cosilicate and is synthesized by linking D4R units in tetrabutylammonium cyclosilicate crystals with dimethyldichlorosilane. The structure of PSS‐2 was revealed using solid state NMR spectroscopy. Physical properties of the polymer were investigated using thermogravimetric analysis, X‐ray diffraction as well as high‐pressure water intrusion–extrusion experiments.